Sociocultural and Socioeconomic Influences on Type 2 Diabetes Risk in Overweight/Obese African-American and Latino-American Children and Adolescents. (13th May 2013) - Hasson, Rebecca E.; Adam, Tanja C.; Pearson, Jay; Davis, Jaimie N.; Spruijt-Metz, Donna; Goran, Michael I.
Abstract : Purpose . It is unclear whether sociocultural and socioeconomic factors are directly linked to type 2 diabetes risk in overweight/obese ethnic minority children and adolescents. This study examines the relationships between sociocultural orientation, household social position, and type 2 diabetes risk in overweight/obese African-American (n = 43 ) and Latino-American (n = 113 ) children and adolescents. Methods . Sociocultural orientation was assessed using the Acculturation, Habits, and Interests Multicultural Scale for Adolescents (AHIMSA) questionnaire. Household social position was calculated using the Hollingshead Two-Factor Index of Social Position. Insulin sensitivity (SI ), acute insulin response (AIRG ) and disposition index (DI) were derived from a frequently sampled intravenous glucose tolerance test (FSIGT). The relationships between AHIMSA subscales (i.e., integration, assimilation, separation, and marginalization), household social position and FSIGT parameters were assessed using multiple linear regression. Results. For African-Americans, integration (integrating their family's culture with those of mainstream white-American culture) was positively associated with AIRG (β = 0.27 ± 0.09, r = 0.48, P < 0.01 ) and DI (β = 0.28 ± 0.09, r = 0.55, P < 0.01 ). For Latino-Americans, household social position was inversely associated with AIRG (β = - 0.010 ± 0.004, r = - 0.19, P = 0.02 ) and DI (β = - 20.44 ± 7.50, r = - 0.27, P < 0.01 ). Conclusions. Sociocultural orientation and household social position play distinct and opposing roles in shaping type 2 diabetes risk in African-American and Latino-American children and adolescents.